2020
DOI: 10.5114/pjr.2020.93258
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of magnetic resonance imaging in the evaluation of pulmonary infections in immunocompromised patients

Abstract: Purpose: To evaluate the accuracy of magnetic resonance imaging (MRI) for diagnosing pulmonary infections in immunocompromised adults. Material and methods: Computed tomography (CT) and MRI chest were performed in 35 immuno-compromised patients suspected of pulmonary infection. The MRI sequences that were performed included axial and coronal T2 half-Fourier acquisition single-shot turbo spin-echo (HASTE), spectrally attenuated inversion recovery (SPAIR), true fast imaging with steady-state free precession (TRU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Moreover, the presence of early-stage necrotic pneumonia, which could not be shown by contrast-enhanced CT in 25% of patients, was demonstrated by MRI (27). In subsequent studies with a similar patient group, MRI was found to be very useful diagnostic tool, especially in its use during follow-up (28,29); furthermore, MRI was reported to be promising in detecting nodules in these patients (30). In our study, the sensitivity of MRI in nodule detection was 91.67%, and its specificity was 100%.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the presence of early-stage necrotic pneumonia, which could not be shown by contrast-enhanced CT in 25% of patients, was demonstrated by MRI (27). In subsequent studies with a similar patient group, MRI was found to be very useful diagnostic tool, especially in its use during follow-up (28,29); furthermore, MRI was reported to be promising in detecting nodules in these patients (30). In our study, the sensitivity of MRI in nodule detection was 91.67%, and its specificity was 100%.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding opacities, the authors of several other studies have also reported that the sensitivity of MRI is equivalent to that of CT for the detection of consolidations, although not for ground-glass opacities, some of which cannot be seen on MRI (16,24) . Recently, Singh et al (21) evaluated the diagnostic accuracy of MRI for respiratory infections in immunocompromised patients. Their MRI protocol, like ours, included a TrueFISP sequence, and the authors found it to have a sensitivity of 100% for the detection of consolidations and of only 16.6% for the detection of ground-glass opacities.…”
Section: Discussionmentioning
confidence: 99%
“…Lung abnormalities observed on MRI were described according to the current literature on the subject, which adopts the CT terminology outlined in the Fleischner Society glossary. For instance, we defined ground-glass opacities as a hazy increase in signal intensity in the lung, with preserved bronchial and vascular margins (14,(16)(17)(18)(19)21,22) . The two readers evaluated the distribution of the pulmonary findings (unilateral vs. bilateral; unilobar vs. multilobar; affected lobes; involvement of upper, middle, and lower zones; peripheral or central lung involvement; anterior or posterior lung involvement; and subpleural sparing), as well as their opacity (groundglass opacities, consolidation, and interlobular/intralobular septal thickening) and appearance (patchy/segmental, rounded, crazy-paving, halo/reversed halo, linear/reticular, and air bronchogram).…”
Section: Image Analysismentioning
confidence: 99%
“…Given the only slightly inferior sensitivity for pulmonary nodules compared to CT, MRI might be recommended for long-term follow-up of children and young adults after malignancies with potential mediastinal and pulmonary metastases, e.g., in children with seminoma. For this purpose, a threshold size of 4-5 mm can be expected for pulmonary nodule detection with MRI [33,[70][71][72] (Fig. 11).…”
Section: Pulmonary Massesmentioning
confidence: 99%